DEFINISI AL-QUR’AN, SURAT, DAN AYAT SERTA URGENSINYA DALAM PENDIDIKAN - Aina Mardhiyah; Sriyono Fauzi (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2026)
The Qur’an is the holy book of Islam, revealed by Allah to the Prophet Muhammad (peace be upon him) as a guide for the lives of Muslims. Today, many Islamic educational institutions have adopted Qur’an-based education. As the era of globalization becomes increasingly complex, Islamic education faces the challenge of remaining relevant. Education grounded in the values of the Qur’an serves as a crucial foundation for shaping students who are well-informed and possess strong moral character. The objective of this study is to conduct an in-depth discussion on the definitions of the Qur’an, surahs, and verses, as well as the significance of the Qur’an in Islamic education. This study employs a literature review method (library research) that relies on sources from books and articles in scientific journals related to the subject matter, analyzing data through the perspectives of experts, using a constructive approach and interpretation of the core content. The findings indicate that the Qur’an is of paramount importance in Islamic education, and Islamic education cannot function without its integration with the Qur’an. In addition to being a vast source of knowledge, the Qur’an also teaches learning methods that remain relevant today and guides the character development of students to become good individuals and devout Muslims.